Saikosaponin D exerts antidepressant effect by regulating Homer1-mGluR5 and mTOR signaling in a rat model of chronic unpredictable mild stress - Chen-Yue Liu; Jian-Bei Chen; Yue-Yun Liu; Xue-Ming Zhou; Man Zhang; You-Ming Jiang; Qing-Yu Ma; Zhe Xue; Zong-Yao Zhao; Xiao-Juan Li; Jia-Xu Chen (BMC, 2022)
Abstract Background Many studies about depression have focused on the dysfunctional synaptic signaling in the hippocampus that drives the pathophysiology of depression. Radix Bupleuri has been used in China for over 2000 years to regulate liver-qi. Extracted from Radix Bupleuri, Saikosaponin D (SSD) is a pharmacologically active substance that has antidepressant effects. However, its underlying mechanism remains unknown. Materials and methods A chronic unpredictable mild stress (CUMS) paradigm was used as a rat model of depression. SD rats were randomly assigned to a normal control (NC) group or one exposed to a CUMS paradigm. Of the latter group, rats were assigned to four subgroups: no treatment (CUMS), fluoxetine-treated (FLU), high-dose and low-dose SSD-treated (SSDH and SSDL). SSD was orally administrated of 1.50 mg/kg and 0.75 mg/kg/days for three weeks in the SSDH and SSDL groups, respectively. Fluoxetine was administrated at a dose of 2.0 mg/kg/days. SSD's antidepressant effects were assessed using the open field test, forced swim test, and sucrose preference test. Glutamate levels were quantified by ELISA. Western blot and immunochemical analyses were conducted to quantify proteins in the Homer protein homolog 1 (Homer1)-metabotropic glutamate receptor 5 (mGluR5) and mammalian target of rapamycin (mTOR) pathways in the hippocampal CA1 region. To measure related gene expression, RT-qPCR was employed. Results CUMS-exposed rats treated with SSD exhibited increases in food intake, body weight, and improvements in the time spent in the central are and total distance traveled in the OFT, and less pronounced pleasure-deprivation behaviors. SSD also decreased glutamate levels in CA1. In CA1 region of CUMS-exposed rats, SSD treatment increased mGluR5 expression while decreasing Homer1 expression. SSD also increased expressions of postsynaptic density protein 95 (PSD95) and synapsin I (SYP), and the ratios of p-mTOR/mTOR, p-p70S6k/p70S6k, and p-4E-BP1/4E-BP1 in the CA1 region in CUMS-exposed rats. Conclusions SSD treatment reduces glutamate levels in the CA1 region and promotes the expression of the synaptic proteins PSD-95 and SYP via the regulation of the Homer1-mGluR5 and downstream mTOR signaling pathways. These findings suggest that SSD could act as a natural neuroprotective agent in the prevention of depression.